Molecular mechanism study of the potential pathogenic role of myeloid cell receptor Clec7a in the SOD1G93A ALS mouse model - Yan, Huilan. (Tufts University. Tisch Library., 2024)
Thesis (M.S.)--Tufts University, 2024-05.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisor: Yongjie Yang.; Committee: Pothos Emmanuel.; Keywords: Pharmaceutical sciences, Neurosciences, and Immunology.